(untitled) (Zaporizhzhia Historical Review, 2021)
The article is dedicated to analytical characteristics of church estates in western part of Ukraine in the second half of the 18th century in the system of economic relations of this region. It considers the conditions of the development of agriculture. The level of the development of such branches of agriculture as flourgrinding, home-brew, metal production and construction trade is analyzed.